Fasting in the Life and Works of Andrey Muraviev .......... 89 - Kościołek, Anna (Czas w kulturze rosyjskiej, 2019)
FASTING IN THE LIFE AND WORKS OF ANDREY MURAVIEVThe article is an attempt to present Andrey Muraviev’s (1806–1874), writer, poet, theologian, church and state activist, approach to fasting, both in his private life and in his works, mainly on the basis of his memoirs and Letters on Divine Service of the Eastern Church. Although Muraviev was brought up in a religious atmosphere, he was not used to abiding by the rules of fasting as a child and young man; it was only on his way to Holy Land that he started to observe them throughout the whole Lent. Afterwards he gradually became used to other forms of several-days fasting, including fasting every week, on Wednesdays and Fridays. In his reflections on the subject of fast, the poet referred to biblical texts (Old and New Testament), the works of the Church Fathers, including John of Damascus, John Chrysostom, Theodore the Studite and Andrew of Crete, church songs. He reminded that the fast was adopted from the Old Testament as a tool supporting the Christian prayer. Muraviev discovered upon his own example that fasting is an important element of human spiritual life. He emphasized not only abstaining from certain kinds of food, but first of all subjecting the body to the soul, taming one’s passions.